Godless fictions in the eighteenth century: a literary history of atheism - Reeves, James Bryant ca. 20./21. Jh. (Cambridge University Press, 2020)
An age of atheism -- A complete system of atheism: Jonathan Swift -- Godless dunces: Alexander Pope -- The limits of self: Sarah Fielding -- Gender and the Orient: Phebe Gibbes -- Ecumenical poetics: William Cowper -- Sympathy and unbelief: Percy Shelley.